Hydrodynamic relationships between gravel pit lakes and aquifers: brief review and insights from numerical investigations - Jost, Anne; Wang, Shuaitao; Verbeke, Thomas; Colleoni, François; Flipo, Nicolas (Comptes Rendus. Géoscience)
Supply of aggregate materials for every construction requires mining of sand and gravel, which leads to the formation of a myriad of freshwater lakes, a now common feature of the landscape in the valleys of large rivers. Typically small in size and shallow, they are filled with waters from the adjacent aquifers and directly exposed to the atmosphere. The creation of gravel pit lakes has various and contrasting effects on their immediate environment. This article first provides a review of these impacts from the hydrodynamic point of view, and illustrates them on simple numerical test cases. It also introduces the gravel pit lake module developed for the occasion within the integrated modelling platform CaWaQS, which formulation was tested on the same test cases against the Lak package, its Modflow counterpart. By accurately simulating gravel pit lake interactions with groundwater in different configurations, this modelling exercise also aims to identify the preponderant factors leading water level fluctuations of those artificial lakes, whose temporal monitoring will soon be accessible to satellite observation.